Estrutura de comunidade de peixes em três lagoas marginais do Rio Paraná, no trecho entre os reservetários de Júpiá e Porto Primavera - Vilela, Maria José Alencar (2001)
The fish communities in three marginal lagoons of Paraná river, located between Jupiá and Porto Primavera reservoirs, were studied in order to evaluate the effect of biotic and abiotic factors, as well as the degree of connection with Paraná river, on community structure. Fish diversity was sampled using big sieve nets and gill nets with various mesh sizes. Sample period range from April 1998 to October 1999, so that the sample effort was the same in dry and rainy seasons. The Characiformes predominated in the studied communities, mainly in the form of small sized species. The ecological indices of diversity, richness and equitability exhibited higher values in the largest and wider covered lagoon, close to Verde river mouth, an important tributary of Paraná river s right bank. Also, the connection between this lagoon and the river channel, although indirect, was almost permanent. According to PCA, most differences among fish assemblages were related to the amount of submerged and floating macrophytes. A total of 40 species was identified, however Hoplias malabaricus and Hyphessobrycon eques occurred in all environments, from wich H. eques predominated in total samples. Conversely, four long-term migratory species were poorly recorded, including Prochilodus lineatus. The use of these lagoons as nursery and growing areas by initial forms and juveniles of large fishes from Paraná basin was not observed in this period. Presumably, this resulted from the absence of more direct and persistent connection between lagoons and the Paraná river or breeding failure of some species. Parental care was uncommon among sedentary fishes, although such behavior predominates among Cichlidae species. Piscivorous fishes composed the richest trophic categories, including three species introduced in the basin (Cichla monoculus, Plagioscion squamosissimus and Astronotus ocellatus), followed by insectivorous (Roeboides paranensis) and omnivorous (H. eques) ones. Otherwise, considering individuals number, insectivorous and omnivorous species predominated, presumably due the enhanced food resources availability. The richest lagoon of the studied area will be submerged due the complete inundation of Porto Primavera reservoir, which also may influence the lagoons closer to Jupiá UHE. Hence, fish community structure presumably will be severely impacted.